Measurements of genomic GC content in plant genomes with flow cytometry: a test for reliability - Smarda, Petr; Bureš, Petr; Smerda, Jakub; Horová, Lucie (The New phytologist, 2012)
• Knowledge of the phylogenetic pattern and biological relevance of the base composition of large eukaryotic genomes (including those of plants) is poor. With the use of flow cytometry (FCM), the amount of available data on the guanine + cytosine (GC) content of plants has nearly doubled in the last decade. However, skepticism exists concerning the reliability of the method because of uncertainty in some input parameters. • Here, we tested the reliability of FCM for estimating GC content by comparison with the biochemical method of DNA temperature melting analysis (TMA). We conducted measurements in 14 plant species with a maximum currently known GC content range (33.6-47.5% as measured by FCM). We also compared the estimations of the GC content by FCM with genomic sequences in 11 Oryza species. • FCM and TMA data exhibited a high degree of correspondence which remained stable over the relatively wide range of binding lengths (3.39-4.09) assumed for the base-specific dye used. A high correlation was also observed between FCM results and the sequence data in Oryza, although the latter GC contents were consistently lower. • Reliable estimates of the genomic base composition in plants by FCM are comparable with estimates obtained using other methods, and so wider application of FCM in future plant genomic research, although it would pose a challenge, would be supported by these findings.
Keywords: teplota; Bacteria; genom rostlinný; DNA, Plant; druhová specificita; reprodukovatelnost výsledků; Nucleic Acid Denaturation; Genome, Plant; Flow Cytometry; sekvence nukleotidů; Species Specificity; Base Composition; průtoková cytometrie; DNA rostlinná; denaturace nukleových kyselin; Reproducibility of Results; zastoupení bazí; Base Sequence; Temperature